Bomb blast injuries to the ear: the London Bridge incident series. Issue 3 (September 1995) - Walsh, R M; Pracy, J P; Huggon, A M; Gleeson, M J
Abstract : Twelve patients who were treated for ear injuries at Guy's Hospital following the London Bridge bomb blast in February 1992 were reviewed. Among three there were four perforated eardrums, two of which closed spontaneously (50%). All three patients had a persistent mixed hearing loss. The remaining nine patients had acute sensorineural hearing loss and/or tinnitus only. Four of these had resolved completely by 4h, another one by 48h, and two by 4 weeks. Two patients had a residual high frequency hearing loss. In total, five patients (42%) have a persistent hearing loss. None of the patients suffered from balance problems. In summary, the ear is very susceptible to bomb blast injury, but there is a high rate of spontaneous closure of perforations and improvement of sensorineural hearing loss and tinnitus.